2006
DOI: 10.1007/bf03344179
|View full text |Cite
|
Sign up to set email alerts
|

Reduced levels of adiponectin in sleep apnea syndrome

Abstract: OSAS is associated with reduced levels of adiponectin independently of insulin-resistance and BMI. These low adiponectin levels may contribute to the increased mortality seen in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 42 publications
0
36
1
3
Order By: Relevance
“…It has been suggested that low serum adiponectin levels were tightly associated with increased risk of atherosclerosis and myocardial infarction [32,33]. Previous data from observational studies indicated that OSA was independently associated with adiponectin levels [6][7][8]. A cross-sectional analysis of 86 adult male patients suspected for OSA showed that serum adiponectin levels were significantly lower in the OSA group than in the control.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been suggested that low serum adiponectin levels were tightly associated with increased risk of atherosclerosis and myocardial infarction [32,33]. Previous data from observational studies indicated that OSA was independently associated with adiponectin levels [6][7][8]. A cross-sectional analysis of 86 adult male patients suspected for OSA showed that serum adiponectin levels were significantly lower in the OSA group than in the control.…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that reduced serum adiponectin levels could partly explain increased cardiovascular disease in OSA patients. Previous studies showed that OSA was associated with significant decrease in serum adiponectin levels [6][7][8].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several other studies have demonstrated lower levels of APN in OSAS patients and subsequent improvement following CPAP therapy [104][105][106][107][108][109][110]. However, not all studies have shown an association between OSAS and APN [111][112][113][114][115].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…OSAS has independently been associated with reduced levels of adiponectin (Masserini et al, 2006;Zhang et al, 2006;Carneiro et al, 2009) which may favour cardiovascular disease development. The recurrent hypoxia-reoxygenation attacks in OSAS patients may activate oxidative stress and lead to low levels of adiponectin (Vatansever et al, 2010).…”
Section: Obesitymentioning
confidence: 99%